Salivary neutrophils isolation of severe early childhood caries patients with flow cytometry analysis using magnetic beads and CD177 marker - Muhammad Luthfi; Tuti Kusumaningsih (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Neutrophils are the first line of defense, not only serving as he killer of microbes through phagocytosis process, in which reactive oxygen species (ROS) and anti-microbial peptides were released, but also regulating activation of immune response. CD177 is a tidylinositol glycosylphosphate glycoprotein with a molecular weight of 58- 64-kDa exclusively found on neutrophils, neutrophilic metamyelocytes, and mielosit. CD177 expression, a protein on the cell surface with an average size ranging from 45% to 65%, is only found on subpopulations of neutrophils. Purpose: This study aims to analyze the effects of salivary neutrophil isolation using magnetic beads and CD177 marker on S-ECC patients. Method: The study is an observational analytic research with cross sectional approach using flow cytometry analysis on the S-ECC patients and the caries-free children who were asked to use mouthwash, NaCl 1.5%. For the isolation of neutrophils, magnetic beads labeled with FITC funds and CD177+ marker were used. Result: There were 77.66% of salivary neutrophils expressing CD177+ markers, successfully isolated in the S-ECC patients, while in the caries-free children there were 63.67% of salivary neutrophils. Conclusion: In the S-ECC patients, there were 77.66% of salivary neutrophils expressing CD177markers, successfully isolated, while in the caries-free children there were 63.67% of salivary neutrophils.